2011
DOI: 10.1371/journal.pone.0027415
|View full text |Cite
|
Sign up to set email alerts
|

The Association of APOE Genotype with Cognitive Function in Persons Aged 35 Years or Older

Abstract: APOE genotype is associated with the risk of Alzheimer's disease. In the present study, we investigated whether APOE genotype was associated with cognitive function in predominantly middle-aged persons. In a population-based cohort of 4,135 persons aged 35 to 82 years (mean age (SD), 55 (12) years), cognitive function was measured with the Ruff Figural Fluency Test (RFFT; worst score, 0 points; best score, 175 points). APOE genotype (rs429358 and rs7412) was determined by polymerase chain reaction. The mean RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
(48 reference statements)
3
33
0
Order By: Relevance
“…30 In this study, the APOE E4 allele (E4/E4, E4/E3, and E4/E2) frequency was 47% in AD cases and 19% in controls. This APOE E4 allele frequency of our study subjects is lower than those reported from previous European studies, [31][32][33][34][35] whereas our data are similar to results from Japanese study. 36 In consistent with previous studies, our study showed 2 APOE SNPs (rs429358 and rs2075650) were significantly associated with AD susceptibility after Bonferroni correction, confirming the influence of APOE gene in AD risk of Korean population.…”
Section: Discussionsupporting
confidence: 86%
“…30 In this study, the APOE E4 allele (E4/E4, E4/E3, and E4/E2) frequency was 47% in AD cases and 19% in controls. This APOE E4 allele frequency of our study subjects is lower than those reported from previous European studies, [31][32][33][34][35] whereas our data are similar to results from Japanese study. 36 In consistent with previous studies, our study showed 2 APOE SNPs (rs429358 and rs2075650) were significantly associated with AD susceptibility after Bonferroni correction, confirming the influence of APOE gene in AD risk of Korean population.…”
Section: Discussionsupporting
confidence: 86%
“…The age span from 40 to 77 years is a period of life with substantial decrease in physical and cognitive functions (Frederiksen et al , 2002; Izaks et al , 2011; Jeppesen et al , 2011), and we hypothesized that this decline is reflected in DNA repair parameters. This study involves a molecular investigation of repair capacity of SSBs and DSBs in isolated PBMCs from the study subjects by three molecular assays.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was observed that human apoE4 knock-in mice show a decrease in long-term potentiation, excitatory synaptic transmission and dendritic arborization, which determine impaired synaptic and cognitive functions [45][46][47][48]. These experimental data corroborate with clinical evidence, demonstrating that apoε4 homozygosity confers a substantial cognitive function decline in persons aged 35 years or older [49]. The putative connection between cholesterol metabolism and AD is supported by evidence relating other genes involved in the regulation of cholesterol metabolism and the onset of AD.…”
Section: Alzheimer's Diseasementioning
confidence: 52%